CIPp Model In Utilizing Interactive Multimedia-Based Teaching Materials (Evaluation Study On Pertiwi 1) - Dwi Rulismi (STKIP Rokania Pasir Pangaraian, 2022)
The purpose of this study was to determine the use of interactive multimedia-based teaching materials in early childhood with the application of the CIPP evaluation model (Context, Input, Process, Product). This study used the CIPP method which has four evaluation attributes: 1) Context, 2) Input, 3) Process 4) Product. And the rating weight category with a Likert Scale with a questionnaire used in the form of 5 answer choices. Objects in product evaluation of interactive multimedia-based teaching materials that will be developed. The research was conducted by testing the evaluation model. By testing the quality of the model developed is truly tested empirically. The validation instrument is to determine the feasibility of interactive multimedia-based teaching materials developed for use by Early Childhood Children to achieve an effective learning process. Collecting data in this study using validation instruments. The data analysis technique in this study used the CIPP model to evaluate the use of interactive multimedia-based teaching materials with 12 indicators and 53 questions related to the use of interactive multimedia-based teaching materials for early childhood with an average score of 72%. Declared relevant and can be utilized in learning in early childhood. The revisions desired by the evaluator are: 1) instructions for using teaching materials are made, because in the manufacture of interactive multimedia-based teaching materials there are no guidelines for operating these interactive multimedia teaching materials. With the revision of this evaluator, the researcher made instructions or guidelines for the operation of this interactive multimedia-based teaching material. 2) suitability of the material with the daily learning implementation plan (RPPH) on interactive multimedia-based teaching materials